Adolescents’ Sources of Sexuality Education and their Sexual Beliefs and Practices: Rethinking the Analog and Digital Sources - Rachel Atomatofa; Crescentia Ojenikoh Sekegor; Oghenevwairhe Emefe (Science Education International)
This study investigated the awareness level and sources of sex education, beliefs, and practices of adolescents across gender, location, and school type. Sources of sex education were categorized as either analog or digital. Guided by four research questions, a stratified random sample of 162 adolescents with the sampling frame constructed to ensure proportionate representation of adolescents was conducted. Data were collected using a 7-point Likert scale instrument, adolescents knowledge of Sexuality Education Questionnaire. The instrument was rigorously tested for face and content validity, been reviewed, and validated by experts in measurement and evaluation and health education. The Cronbach alpha reliability coefficient was 0.70, indicating moderate reliability on a pilot study of 50 adolescents. Descriptive and inferential statistics were employed to explore relationships. Results showed, the adolescents demonstrated a moderate and comparable level of awareness of sexuality education across groups. The results also showed that digital sources especially the internet had the greatest influence on the adolescents’ sexual awareness, beliefs, and practices across gender, location, and school types. The findings underscore the need for educators and policymakers to create comprehensive and inclusive sex education programs in all schools that integrate both analog and digital sources to cater to the diverse needs of adolescents.